Study on Approximate Solution of Fractional Order Biological Population Model - , Yunqi Xu; , Dianchen Lu (Archives of Current Research International, 2018)
In this paper, we present an algorithm of the homotopy analysis Elzaki transform method (HAETM) which is a combination of Elzaki transform method and homotopy analysis method (HAM) to solve a more general biological population model. The fractional derivatives are described by Caputo sense. The proposed method presents a procedure of constructing the set of base functions and gives the high-order deformation equations in a simple form and provides the solution in the form of a convergent series. Three examples are used to illustrate the preciseness and effectiveness of the proposed method.